Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Return Saham Dengan Return On Asset Sebagai Variabel Moderating - Alia Sifa Ikrima; Asrori Asrori (Gorontalo Accounting Journal, 2020)
The purpose of this study was to analyze about the effect of economic, environmental, and social corporate social responsibility disclosure of stock returns with ROA as a moderating variable. The data analysis methods used were Moderation Regression Analysis (MRA). The results of the study showed that the economic CSRD and environmental CSRD had no effect on stock returns. While, CSRD and the social CSRD had a positive and significant effect on stock returns. In addition, ROA was able to moderate the positive effect of social CSRD on stock returns. However, ROA was not able to moderate the effect of CSRD, economic and environmental CSRD on stock returns. The conclusion from this study was the higher the disclosure of CSRD and social CSRD, the higher the stock returns will be. On the other hand, ROA strengthens the effect of social CSRD on stock returns.